Comparison of the Effectiveness of Educational Media on Knowledge and Attitude Towards Handling Stroke Attacks: A Systematic Review - Daniel Christian; I Made Kariasa; Liya Arista (GLOBAL HEALTH SCIENCE GROUP, 2026)
The success of stroke management is largely determined by the speed of symptom recognition and the decision to access emergency care. Gaps in conventional education access and low health literacy make it crucial to compare the effectiveness of digital versus non-digital educational media. This study aims to analyze the comparative effectiveness of educational media on knowledge and attitudes towards handling strokes through a systematic review. A Systematic Review was conducted following the PRISMA 2020 guidelines. Literature searches (January 2021–September 2025) in PubMed, Scopus, ScienceDirect, Taylor & Francis and Google Scholar identified 4.185 articles. Seven studies were included following a screening and eligibility assessment process. The designs comprised RCTs, quasi-experiments, and pre–post studies on adult community and family populations. Data were standardized, synthesized thematically, and quality-assessed using the JBI checklist. All studies reported significant improvements in the knowledge of stroke signs/symptoms (FAST) after interventions. Digital media (videos/animations, e-learning, web campaigns) more consistently improved quick-response attitudes and the intention to contact EMS compared to non-digital media (leaflets/flipbooks, lectures). Online campaigns and short videos significantly boosted FAST recognition by approximately 70–80% and fortified EMS activation intentions, with some respondents still opting for non-EMS routes. Non-digital media continued to be effective in low-tech environment infrequently used to gauge or alter actual behaviour. Both media types effectively enhance knowledge, but web-based media are superior in shaping rapid-response attitudes and intentions. Future programs should prioritize hybrid models that combine digital framework with face-to-face guidance and digital literacy training for patients, families, and healthcare providers to strengthen patient autonomy and digital health service efficiency.